O51 Use of hierarchical task analysis and in-situ simulation for adult intensive care staff in managing unplanned extubations. (5th November 2017) - Ansari, U; Baxendale, B; Miles, G; Velzen, J; Atkinson, S; Lang, A; Gill, S; Beer, T de
Abstract : Background and Purpose: Unplanned extubation (UE) is a recognised complication of critical care airway management.(NAP4, Royal College of Anaesthetists, UK) Although an infrequent occurrence in adult intensive care units (ICU) it presents a unique challenge to staff in safely securing the patient's airway under varying staff skill mix and ICU experience. This study provides a human factors systems work analysis and qualitative evaluation of ICU staff in a National Health Service (NHS) Hospital Trust to inform the development of a mastery learning programme (MLP) for UE response and management (see Figure). Methodology: A hierarchical task analysis (TA) for the management of UEs in orally intubated patients was co-created with Anaesthetic and critical care experts. The TA was shared with twenty-one ICU nurses and doctors ranging in seniority and airway training who were interviewed about their experiences with UEs and the sociotechnical and contextual factors affecting their clinical practice and decision making. Recorded in-situ simulation was used to test the methodology and inform learning. Results: Interview findings provided comprehensive understanding of the clinical tasks, essential personnel, and the equipment and information necessary for responding to UE incidents. Leadership of senior nurses and doctors was essential to explicitly verbalise directions to junior staff members; however, individual situation awareness and unspoken tacit knowledge of roles and responsibilities also informed UE response. Expert review of video captured during the in-situ simulation informed the MLP. Discussion: The experiences of Nottingham ICU staff revealed the essential nature of non-technical skills that are employed to cope with uncertainty in experience level and technical knowledge of team members who will respond to an UE event. Skill gaps were identified due to inconsistent training and lack of familiarity with UEs and reintubation. Identification of staff coping skills, teamwork, leadership, task allocation, and communication are required for the development of a MLP for adult ICU staff for UE and airway management. Conclusions: This study can be used to upskill both nurses and doctors in UE response, enhance organisational learning, provide in-situ simulation and improve timeliness and safety in UE rescue based on a human factors approach. Reference: 1. 4th National Audit Project of the Royal College of Anaesthetists: Major complications of airway management in the UK 2011:71. Royal College of Anaesthetists, UK. https://www.rcoa.ac.uk/system/files/CSQ-NAP4-Full.pdf